Structural controls on the stratigraphic architecture of net-transgressive shallow-marine strata, Middle-to-Upper Jurassic, Egersund Basin, Norwegian North Sea - Mannie,AS; Jackson,CAL; Hampson,GJ (Basin Research, 2014)
In this study we integrate 3D seismic reflection, wireline log, biostratigraphic and core data from the Egersund Basin, Norwegian North Sea to determine the impact of syn-depositional salt movement and associated growth faulting on the sedimentology and stratigraphic architecture of the Middle-to-Upper Jurassic, net-transgressive, syn-rift succession. Borehole data indicate that Middle-to-Upper Jurassic strata consist of low-energy, wave-dominated offshore and shoreface deposits, and coal-bearing coastal plain deposits. These deposits are arranged in four parasequences that are aggradationally to retrogradationally stacked to form a net-transgressive succession that is up to 150 m thick, at least 20 km in depositional strike (SW-NE) extent, and >70 km in depositional dip (NW-SE) extent. In this rift-margin location, changes in thickness but not facies are noted across active salt structures. Abrupt facies changes, from shoreface sandstones to offshore mudstones, only occur across large displacement, basement-involved normal faults. Comparisons to other tectonically active salt-influenced basins suggest that facies changes across syn-depositional salt structures are observed only where expansion indices are >2. Subsidence between salt walls resulted in local preservation of coastal-plain deposits that cap shoreface parasequences, which were locally removed by transgressive erosion in adjacent areas of lower subsidence. The depositional dip that characterises the Egersund Basin is unusual and likely resulted from its marginal location within the evolving North Sea rift and an extra-basinal sediment supply from the Norwegian mainland.